Santa Vera Cruz Tatita - Albó, Xavier (1974)
This work is a sociological and anthropological analysis of one of the main celebrations of the type of pilgrimage within the valleys of Cochabamba. Descriptions and analyzes of festivals and ritual celebrations abound in Andean literature. But in the vast majority of cases they are local or regional festivals of a patronal type, descriptions of pilgrimages are less frequent, although some are not lacking, such as that of Ramírez (1969) on the novena of Qoyllur Rit'i near from Cuzco. There are parts of the Andes where pilgrimages are almost non-existent, such as among the Aymara (Albó, in press).